Boron-aluminum alloy with spherical composite layer structure and preparation method thereof
By using high-active aluminum powder and ultrafine boron powder, combined with plasma high-temperature combination and gasification recondensation technology, boron-aluminum alloy composite particles with spherical composite layer structure were prepared, which solved many problems in the traditional boron-aluminum alloy powder preparation method, and significantly improved the spheroidization rate, fluidity and combustion efficiency of the material.
Patent Information
- Application Number
- CN202510047551.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-25
AI Technical Summary
The traditional preparation method of boron aluminum alloy powder has problems such as irregular powder morphology, high hardness, easy agglomeration, poor fluidity, difficult particle size to control and uneven components, which affects its application effect.
Highly reactive aluminum powder and ultrafine boron powder are used as raw materials to form nano and micron-sized boron aluminum alloy powders through plasma high-temperature combination treatment, and boron aluminum alloy composite particles with aluminum as shell coated with boron aluminum alloy phase through plasma vaporization and recondensation are made.
The spheroidization rate and fluidity of the alloy material are significantly improved, the combination ratio is high, and the particle size is controllable, which avoids the problems of impurities introduction and uneven components, and improves the combustion efficiency and combustion calorific value.
Smart Images

Figure CN119870463A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of energetic materials and preparation thereof, and in particular, relates to a boron-aluminum alloy with a spherical composite layer structure and a preparation method thereof. Background Art
[0002] The combustion calorific value of amorphous boron can reach 58MJ / kg, which is much higher than other chemical elements used in energetic materials. It is widely used in the synthesis of new energetic materials and can be used in solid fuel propulsion systems. It has good application prospects in the field of self-propagating thermal reduction method for purifying metals. However, the melting point and ignition temperature of boron are relatively high. Its oxidation product B2O3 has a low melting point and a high boiling point. It can adhere to the surface of boron particles to form a liquid film, blocking the contact between boron and oxygen, resulting in low combustion efficiency of boron. The high calorific value property cannot be fully utilized, and the actual combustion calorific value is much lower than that of pure aluminum. In order to improve the actual combustion efficiency of boron, metals with strong activity are usually used as additives, and the synergistic effect of additives and boron is used to promote more complete combustion of boron. There are two ways to achieve this: one is to prepare a mixed powder by mixing boron powder with metal components, and the other is to form a metal boron alloy composed of boron and metal elements through chemical reactions. Under the same element ratio, boron and metal elements in metal borides form stable chemical bonds, and the microstructure is stable and uniform; the mixed powder does not form a stable and uniform composite microstructure of boron and metal elements, so the combustion synergistic promotion effect of boron and metal elements in metal borides is better. Aluminum has a high combustion calorific value and combustion efficiency, and is a widely used metal fuel in energy-containing systems. Boron and aluminum can form alloy phases AlB2 and AlB 12 The combustion of boron powder is driven and promoted by the combustion of aluminum, which greatly improves the combustion efficiency of boron. The measured combustion calorific value is significantly higher than that of pure aluminum.
[0003] At present, researchers at home and abroad use thermal sintering and other methods to prepare boron aluminum alloy powder, alloy phase AlB2 and AlB 12 The proportion can reach 58%, and the measured combustion calorific value is 30-35MJ / kg, which is significantly higher than pure aluminum powder. However, the alloy powder obtained by thermal sintering has the following problems and is difficult to use: (1) The alloy powder prepared by sintering needs to be crushed and refined, and the powder morphology is irregular, with many edges and corners, and the hardness of the alloy powder is high, so the sensitivity during use is high; (2) The alloy powder is easy to agglomerate and has poor fluidity; (3) The particle size of the alloy powder is difficult to control during the crushing process, and impurities will be introduced to reduce the purity; (4) Boron and aluminum cannot be completely combined during the sintering process. The alloy powder is a mixed system composed of borides, pure boron powder, pure aluminum powder, etc. When used in the formula, different phases are peeled off, resulting in uneven components.
[0004] Radio frequency plasma spheroidization technology is suitable for the spheroidization of metal and alloy powders. Its working principle is that under the action of electromagnetic coupling, the Joule heating effect of the induced current heats the airflow to an extremely high temperature to form a self-sustaining plasma. Its heating temperature range can reach 8000~30000K, and the quenching rate can reach 105K / s. It is a good way to prepare composite powders with uniform components and high sphericity. Summary of the invention
[0005] The object of the present invention is to provide a boron aluminum alloy with a spherical composite layer structure and a preparation method thereof, so as to be able to prepare binary or multinary alloy powders of various metals and non-metals through plasma spheroidization technology, thereby significantly improving the spheroidization rate and fluidity, as well as other physical properties of the alloy material.
[0006] To this end, the present invention provides the following technical solutions.
[0007] One aspect of the present invention provides a boron aluminum alloy having a spherical composite layer structure, wherein the boron aluminum alloy has a core-shell structure in which aluminum is used as a shell layer to cover a boron aluminum alloy phase, and the raw material composition of the boron aluminum alloy comprises, by weight percentage: 35-60% aluminum powder and 40-65% boron powder; and the aluminum powder has a D 50 is 0.9~1μm or 10~50μm, and the D 50 ≤4μm.
[0008] Another aspect of the present invention provides a method for preparing a boron aluminum alloy having a spherical composite layer structure, the method comprising the following steps: S1: mixing boron powder and aluminum powder according to a ratio, and drying to obtain a boron-aluminum mixture; S2: preheating the plasma spheroidizing equipment, and then adding the boron-aluminum mixture for high-temperature plasma treatment to form boron-aluminum alloy powder; S3: The plasma spheroidization equipment is cleaned, preheated and pre-debugged, and then aluminum powder is added to gasify the aluminum powder into aluminum vapor, followed by adding boron aluminum alloy powder to condense into powder, and finally cooled to room temperature to obtain a spherical composite layer structure of a boron aluminum alloy phase with a core-shell structure with aluminum as the shell layer covering the boron aluminum alloy phase.
[0009] In some preferred embodiments, in step S1, the mixing further includes a granulation step.
[0010] In some preferred embodiments, the granulation process is: adding a composite solvent to the boron-aluminum mixed powder, stirring and cutting, to obtain boron-aluminum composite particles.
[0011] In some preferred embodiments, the composite solvent consists of: n-hexane, HTPB, curing agent HDI and polyvinyl alcohol solution; The amount of composite solvent added to every 1000g of boron-aluminum mixed powder is: 400ml of n-hexane, 30g of HTPB, 4ml of curing agent HDI, and the mass concentration of the polyvinyl alcohol solution is 5%.
[0012] In some preferred embodiments, the stirring speed is 300-400 rpm, and the time is 15-30 min.
[0013] In some preferred embodiments, the cutting speed is 800-2000 rpm, and the time is 15-30 min.
[0014] In some preferred embodiments, in step S1, the drying conditions are: temperature 180-200° C., time 8-12 h.
[0015] In some preferred embodiments, in step S2, the preheating uses hot air to heat the oven, the hot air temperature is 150-200° C., and the preheating time is 0.5-1 h.
[0016] In some preferred embodiments, in step S2, the high temperature plasma treatment conditions are: argon is used as the carrier gas, the power is set at 20~25kW, the carrier gas flow rate is 5~25L / min, the powder feeding rate is 10~20g / min, and the pressure in the furnace chamber is controlled at 80~100KPa.
[0017] In some preferred embodiments, in step S3, the preheating uses hot air to heat the oven, the hot air temperature is 150-200° C., and the preheating time is 0.5-1 h.
[0018] In some preferred embodiments, in step S3, the pre-debugging conditions are: argon is used as the carrier gas, the power is set at 20~25kW, the carrier gas flow rate is 5~25L / min, the powder feeding rate is 10~20g / min, and the plasma torch temperature is 20000~30000K.
[0019] In some preferred embodiments, in step S3, the pressure is adjusted to 100-120 KPa after adding the boron aluminum alloy powder.
[0020] By means of the above technical solution, the present invention has at least the following advantages: The present invention aims to solve the shortcomings of the traditional boron aluminum alloy powder preparation method by combining high-activity aluminum powder (nano, micron size) with ultrafine (D 50≤4μm) boron powder is used as a raw material to prepare a boron-aluminum mixed powder, and the boron-aluminum mixed powder is subjected to a plasma high-temperature chemical treatment to form a boron-aluminum alloy powder of nanometer and micrometer sizes. Then, through plasma gasification and re-condensation, boron-aluminum alloy composite particles with a core-shell structure with boron-aluminum alloy powder as the core and aluminum as the coating layer are obtained. The present invention can prepare boron-aluminum alloy powders of various sizes and high chemical composition by a high-temperature plasma method. The powder has high sphericity, good fluidity, high chemical composition ratio, controllable particle size, and no impurities are introduced during the preparation process. The core-shell structure can avoid direct contact between the boron-aluminum alloy and other components, thereby solving the sensitivity problem of the boron-aluminum alloy powder, and also avoiding the peeling of different phases during use. During combustion, the surface aluminum burns first, which can drive the combustion of the internal boron-aluminum alloy powder, reduce the ignition temperature, and help improve the combustion efficiency of the alloy.
[0021] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the preferred embodiments of the present invention are described in detail as follows. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is an electron microscope image of the boron-aluminum alloy with a spherical composite layer structure prepared in Example 1.
[0023] Figure 2 This is an electron microscope image of the boron-aluminum alloy with a spherical composite layer structure prepared in Example 2. DETAILED DESCRIPTION
[0024] In order to make the technical means, creative features, objectives and effects of the present invention easy to understand, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] The present invention proposes boron-aluminum alloy powders of two sizes, micron and nanometer, and a preparation method thereof. First, a mixed powder of aluminum powder and high-purity boron powder is prepared, and then a high-temperature plasma treatment is used to form a boron-aluminum alloy powder, and then a secondary plasma treatment is performed. In this process, aluminum powder is first introduced to gasify the aluminum powder into aluminum vapor under high temperature, and then the boron-aluminum alloy powder is introduced. Through aluminum gasification and re-condensation, an aluminum coating layer is formed on the surface of the boron-aluminum alloy particles, and a boron-aluminum alloy with a spherical composite layer structure of a core-shell structure with aluminum as the shell layer covering the boron-aluminum alloy phase is obtained. Therefore, the specific preparation process of the boron-aluminum alloy particles is as follows: (1) Raw material pretreatment: This process involves mixing micron- or nano-sized high-activity aluminum powder and D 50High-purity boron powder with a size of ≤4 μm is fully mixed to prepare boron-aluminum mixed powders of different sizes, which are then placed in a vacuum oven for drying.
[0026] The suitable drying temperature is 180-200°C, for example, 180°C, 190°C or 200°C, preferably 200°C.
[0027] The suitable drying time is 8 to 12 hours, for example, 8 hours, 9 hours, 10 hours, 11 hours or 12 hours, preferably 8 hours.
[0028] (2) High-temperature plasma treatment: The plasma spheroidization equipment is sealed and vacuumed to set parameters. During the equipment preheating process, high-purity argon is filled into the vacuum chamber before the plasma is operated to form an inert gas environment. The plasma is maintained at a low atmospheric pressure to form a stable plasma torch. A low-power pump with a small flow rate is used to evacuate the chamber to play a role in powder drainage and plasma gas diversion.
[0029] Boron-aluminum mixed powders of different sizes are fed in, and different processes are used to prepare boron-aluminum alloy powders of different sizes. There are different preparation processes for alloys of different sizes, including: i) Nano-sized alloy powder preparation process After the commissioning of the plasma spheroidization equipment is completed, a powder feeder is used to feed the mixed powder of nano aluminum powder and boron powder into a plasma arc reactor. The boron aluminum mixed powder is gasified by a high-temperature plasma torch to form a boron aluminum mixed steam. The mixed steam undergoes a chemical reaction to form a boron aluminum alloy, which is then cooled in a heat exchange chamber to form nanoparticles of the boron aluminum alloy. After the obtained nano boron aluminum alloy powder is cooled, it is taken out from a vacuum powder collecting dish and stored in a vacuum.
[0030] Argon was selected as the carrier gas in the above treatment.
[0031] The appropriate power setting is 20-25 kW, for example, 20 kW, 21 kW, 22 kW, 23 kW, 24 kW or 25 kW, preferably 20 kW.
[0032] A suitable carrier gas flow rate is 5 to 25 L / min, for example, 5 L / min, 10 L / min, 15 L / min, 20 L / min or 25 L / min. Preferably, the initial carrier gas flow rate is 5 L / min, the increase rate is 0.5 L / min, and the maximum carrier gas flow rate is 25 L / min.
[0033] The appropriate powder feeding rate is 10-20 g / min, for example, 10 g / min, 15 g / min or 20 g / min. Preferably, the initial powder feeding rate is 10 g / min, the increase rate is 1 g / min, and the maximum powder feeding rate is 20 g / min.
[0034] The pressure in the furnace chamber is controlled at 80-100 Kpa, for example, 80 Kpa, 85 Kpa, 90 Kpa, 95 Kpa or 100 Kpa, preferably 100 Kpa.
[0035] Clean the plasma spheroidization equipment, repeat the above preheating steps, and after debugging is completed, feed the nano aluminum powder through the carrier gas, and in the high-power plasma torch, the nano aluminum powder is gasified to form steam. Then, the nano boron aluminum alloy powder is fed into the aluminum steam, and the aluminum steam uses the nano boron aluminum alloy powder as a particle nucleus, thereby forming an aluminum coating layer on the surface of the nano particles, and obtaining nano aluminum-coated boron aluminum alloy composite particles with a core-shell structure.
[0036] In the above treatment, argon is used as carrier gas.
[0037] The appropriate power setting is 20-25 kW, for example, 20 kW, 21 kW, 22 kW, 23 kW, 24 kW or 25 kW, preferably 25 kW.
[0038] A suitable carrier gas flow rate is 5 to 25 L / min, for example, 5 L / min, 10 L / min, 15 L / min, 20 L / min or 25 L / min, preferably 15 L / min.
[0039] A suitable powder feeding rate is 10-20 g / min, for example, 10 g / min, 15 g / min or 20 g / min, preferably 15 g / min.
[0040] The appropriate plasma torch temperature is 20000-30000K, for example, 20000K, 25000K or 30000K, preferably 30000K.
[0041] ii) Micron size alloy powder preparation process First, the mixed boron-aluminum powder is granulated, and the composite powder agglomerates are transported to the plasma torch. Under the action of the hot plasma arc, the boron powder and the aluminum powder are fully contacted and combined, and spherical droplets are formed under the action of surface tension. Then the alloy droplets pass through the high-temperature plasma zone, enter the heat exchange chamber, and quickly cool into a solid state to obtain spherical micron-sized boron-aluminum composite particles composed of boron-aluminum alloy, pure aluminum, and pure boron.
[0042] Granulation is performed by adding a composite solvent to the boron-aluminum mixed powder and then stirring and cutting. A suitable composite solvent composition includes n-hexane, HTPB, curing agent HDI and polyvinyl alcohol solution. The amount of composite solvent added to every 1000g of boron-aluminum mixed powder is: 400ml n-hexane, 30g HTPB, 4ml curing agent HDI, and the mass concentration of polyvinyl alcohol solution is 5%.
[0043] A suitable stirring speed is 300-400 rpm, for example, 300 rpm, 350 rpm or 400 rpm, preferably 350 rpm; a suitable stirring time is 15-30 min, for example, 15 min, 20 min, 25 min or 30 min, preferably 25 min.
[0044] A suitable cutting speed is 800-2000 rpm, for example, 800 rpm, 900 rpm, 1000 rpm, 1500 rpm or 2000 rpm, preferably 1500 rpm; a suitable cutting time is 15-30 min, for example, 15 min, 20 min, 25 min or 30 min, preferably 25 min.
[0045] After granulation, drying is required. The appropriate drying temperature is 180-200°C, for example, 180°C, 190°C or 200°C, preferably 200°C; the appropriate drying time is 8-12h, for example, 8h, 9h, 10h, 11h or 12h, preferably 8h.
[0046] After drying, high temperature plasma treatment is performed, and argon is used as a carrier gas in the above treatment.
[0047] The appropriate power setting is 20-25 kW, for example, 20 kW, 21 kW, 22 kW, 23 kW, 24 kW or 25 kW, preferably 20 kW.
[0048] A suitable carrier gas flow rate is 5 to 25 L / min, for example, 5 L / min, 10 L / min, 15 L / min, 20 L / min or 25 L / min. Preferably, the initial carrier gas flow rate is 5 L / min, the increase rate is 0.5 L / min, and the maximum carrier gas flow rate is 25 L / min.
[0049] The appropriate powder feeding rate is 10-20 g / min, for example, 10 g / min, 15 g / min or 20 g / min. Preferably, the initial powder feeding rate is 10 g / min, the increase rate is 1 g / min, and the maximum powder feeding rate is 20 g / min.
[0050] The pressure in the furnace chamber is controlled at 80-100 Kpa, for example, it can be 80 Kpa, 85 Kpa, 90 Kpa, 95 Kpa or 100 Kpa, preferably 100 Kpa.
[0051] Clean the plasma spheroidization equipment, repeat the above preheating steps, and after the equipment is debugged, feed the nano aluminum powder through the carrier gas, and in the high-power plasma torch, the nano aluminum powder is vaporized to form steam. Then, micron-sized boron-aluminum composite particles are transported in the aluminum vapor, and the aluminum vapor uses the micron boron-aluminum composite particles as particles to form nuclei, thereby forming an aluminum coating layer on the particle surface, and obtaining aluminum-coated boron-aluminum alloy micron particles with a core-shell structure.
[0052] In the above treatment, argon is used as carrier gas.
[0053] The appropriate power setting is 20-25 kW, for example, 20 kW, 21 kW, 22 kW, 23 kW, 24 kW or 25 kW, preferably 25 kW.
[0054] A suitable carrier gas flow rate is 5 to 25 L / min, for example, 5 L / min, 10 L / min, 15 L / min, 20 L / min or 25 L / min, preferably 15 L / min.
[0055] A suitable powder feeding rate is 10-20 g / min, for example, 10 g / min, 15 g / min or 20 g / min, preferably 15 g / min.
[0056] The appropriate plasma torch temperature is 20000-30000K, for example, 20000K, 25000K or 30000K, preferably 30000K.
[0057] (3) After the powder is formed, the gas pressure in the furnace is continuously controlled, and the powder is collected after the powder cools to room temperature, which is a boron-aluminum alloy with a spherical composite layer structure. Finally, the obtained alloy is tested for particle size, sphericity, combustion calorific value, and combustion rate.
[0058] Unless otherwise specified, the percentage content involved in the present invention refers to mass percentage for solid-liquid mixing and solid-solid mixing, and refers to volume percentage for liquid-liquid mixing.
[0059] Unless otherwise specified, the percentage concentrations referred to in the present invention all refer to final concentrations, which refer to the percentage of the added component in the system after the addition of the component.
[0060] The temperature parameters in the present invention, if not specifically limited, allow for both constant temperature treatment and treatment within a certain temperature range. The constant temperature treatment allows the temperature to fluctuate within the precision range controlled by the instrument.
[0061] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods.
[0062] Unless otherwise specified, the plasma spheroidization equipment used in the following examples is: Model APT-125, purchased from Applied Plasma Technologies, Corp., USA; 50 ≤4μm, purchased from Yingkou Liaobin Fine Chemical Co., Ltd.; D 50 The nanostructured particles are 0.9-1 μm or 10-50 μm and were purchased from Jiangsu Chang Aluminum Co., Ltd. Other materials and reagents can be obtained from commercial sources.
[0063] Example 1: Taking the boron-aluminum mixed powder with a mass percentage of 60% boron powder as an example, select D 50 Aluminum powder and boron powder between 0.9-1μm are fully mixed, then placed in a vacuum oven and dried at 200℃ for 8 hours to obtain a boron-aluminum mixed powder. The plasma spheroidization equipment is preheated with hot air, the hot air temperature is 150, the preheating time is 0.5h, argon is used as the carrier gas, the power is set at 20kW, the initial carrier gas flow rate is 5L / min, the initial powder feeding rate is 10g / min, and the gas flow rate is 0.5L / min and the powder feeding rate is 1g / min. The conditions of increasing the speed are increased to a maximum carrier gas flow rate of 25L / min and a maximum powder feeding rate of 20g / min and then kept constant, and the boron-aluminum mixed powder is added to the equipment, the pressure in the furnace chamber is controlled at 100KPa, and cooling begins after the addition is completed. Then the product is moved from the vacuum powder collecting dish to a vacuum environment to obtain a boron-aluminum alloy powder for standby use. Clean the plasma spheroidization equipment, use hot air to preheat the oven, the hot air temperature is 200℃, the preheating time is 1h, after debugging, adjust the equipment power to 25kW, let the plasma torch start to heat up, when the temperature of the plasma torch reaches 30000K, add 1% of the total mass of the boron-aluminum mixed powder with a particle size of 100-200nm at a constant carrier gas flow rate and powder feeding rate of 15L / min and 15g / min, and the nano-aluminum powder is instantly vaporized into aluminum vapor. Then immediately add the spare boron-aluminum alloy powder, and adjust the pressure in the reactor to 100KPa. Under the action of internal pressure, the boron-aluminum alloy particles are coated by the vaporized aluminum powder (aluminum vapor) and condensed into powder. After cooling to room temperature, a boron-aluminum alloy with a spherical composite layer structure is obtained.
[0064] Microstructure: The obtained boron aluminum alloy with spherical composite layer structure is a boron aluminum alloy AlB2 and AlB coated with aluminum as shell. 12 The boron-aluminum alloy nanopowder with a core-shell structure has a powder spheroidization rate of 75%. Figure 1As shown in the figure, the particle size of the boron-aluminum mixed powder without plasma spheroidization after full mixing is distributed between 0.5-5μm (a), and the particle size of the boron-aluminum alloy with a spherical composite layer structure obtained after two plasma spheroidization treatments is distributed between 0.85-0.95μm (b), and the powder is refined. 81% of the boron-aluminum mixed powder changes from large irregular lumps to fine spherical alloy powder.
[0065] The properties of the boron-aluminum mixed powder before plasma spheroidization and the boron-aluminum alloy powder with spherical composite layer structure obtained after two plasma spheroidizations were measured respectively, as follows: a) Bulk density: The bulk density of boron-aluminum mixed powder is 0.83g / cm 3 Increase to 1.06g / cm of fine spherical boron aluminum alloy powder 3 , the loose density and tap density of the powder are significantly improved.
[0066] b) Fluidity: The fluidity of the boron-aluminum mixed powder before spheroidization is 115 s / (100 g), and the fluidity of the boron-aluminum alloy powder with a spherical composite layer structure obtained after spheroidization is 69 s / (100 g), which is significantly higher than that of the boron-aluminum mixed powder that has not undergone plasma spheroidization treatment, and the powder fluidity is improved.
[0067] c) Combustion performance: The combustion calorific value of the obtained boron aluminum alloy with a spherical composite layer structure is 37.1 MJ / kg, and the combustion efficiency is 80.4%.
[0068] Example 2: Taking the boron-aluminum mixed powder with a mass percentage of 65% boron powder as an example, select D 50Aluminum powder and boron powder between 10-50μm are fully mixed, and then granulated: first, the composite solvent formula added to 1000g of boron-aluminum mixed powder is: 400ml n-hexane, 30g HTPB, 4ml curing agent HDI, and the mass concentration of polyvinyl alcohol solution is 5%, and then stirred at 350rpm for 30min. After stirring, it is cut at 1500rpm for 15min to obtain boron-aluminum composite particles. The boron-aluminum composite particles obtained after granulation are dried, that is, the obtained boron-aluminum composite particles are placed in a vacuum oven and dried at 200℃ for 8 hours. The dried boron-aluminum composite particles are subjected to plasma spheroidization treatment: first, the plasma spheroidization equipment is preheated by hot air in the oven, the hot air temperature is 150°C, the preheating time is 0.5h, argon is used as the carrier gas, the power is set to 20kW, and the boron-aluminum composite particles are added to the equipment under the conditions of a carrier gas flow rate of 25L / min and a powder feeding rate of 20g / min. The pressure in the furnace chamber is controlled at 80Kpa. After the addition is completed, cooling begins, and then the product is moved from the vacuum powder collecting dish to a vacuum environment to obtain boron-aluminum alloy powder for standby use. Clean the plasma spheroidization equipment, use hot air to preheat the oven, the hot air temperature is 200℃, the preheating time is 1h, after debugging, adjust the equipment power to 25kW, let the plasma torch start to heat up, when the temperature of the plasma torch reaches 30000K, add 1% of the total mass of the boron-aluminum mixed powder with a particle size of 100-200nm at a constant carrier gas flow rate and powder feeding rate of 25L / min and 20g / min, and the aluminum powder is instantly vaporized into aluminum vapor. Then immediately add the spare boron-aluminum alloy powder, and adjust the pressure in the reactor to 100Kpa. Under the action of the internal pressure, the boron-aluminum alloy particles are coated by the vaporized aluminum powder (aluminum vapor) and condensed into powder. After cooling to room temperature, a boron-aluminum alloy with a spherical composite layer structure is obtained.
[0069] Microstructure: The obtained boron-aluminum alloy with spherical composite layer structure is a micron particle of aluminum-coated boron-aluminum alloy with a core-shell structure. The mixed powder before plasma spheroidization treatment is a single B phase and Al phase. The spherical powder obtained after plasma treatment mainly contains AlB2 and AlB 12 phase, and contains a small amount of monomer phases of boron and aluminum, alloy phases AlB2 and AlB 12 The content can reach 70%-75%. Figure 2 As shown, the boron-aluminum alloy powder with a spherical composite layer structure after plasma spheroidization treatment has a smooth surface and a high sphericity, and the particle size distribution of the spherical powder is between 10-45 μm.
[0070] The properties of the boron-aluminum alloy powder with spherical composite layer structure before plasma spheroidization and after plasma spheroidization were determined as follows: Bulk density: The bulk density of boron-aluminum mixed powder is 0.75g / cm 3 Increase to 0.98g / cm 3 , the loose density and tap density of the powder are significantly improved.
[0071] Fluidity: The fluidity of the boron-aluminum mixed powder before spheroidization is 56 s / (100 g), and the fluidity of the boron-aluminum alloy powder with a spherical composite layer structure obtained after plasma spheroidization is 31 s / (100 g), which is significantly higher than that of the powder that has not been treated with plasma spheroidization, and the powder fluidity is improved.
[0072] c) Combustion performance: The combustion calorific value of the obtained boron aluminum alloy with a spherical composite layer structure is 35.1 MJ / kg, and the combustion efficiency is 77.9%.
[0073] Example 3: Taking the boron-aluminum mixed powder with a mass percentage of 60% boron powder as an example, select D 50 Aluminum powder between 0.9-1μm and boron powder are fully mixed, then placed in a vacuum oven and dried at 200℃ for 8 hours to obtain a boron-aluminum mixed powder. The plasma spheroidization equipment is preheated with hot air, the hot air temperature is 150℃, the preheating time is 0.5h, argon is used as the carrier gas, the power is set at 20kW, the initial carrier gas flow rate is 5L / min, the initial powder feeding rate is 10g / min, and the carrier gas flow rate is 0.5L / min and the powder feeding rate is 1g / min. The conditions of increasing the speed are increased to a maximum carrier gas flow rate of 25L / min and a maximum powder feeding rate of 20g / min and then kept constant, and the boron-aluminum mixed powder is added to the equipment, the pressure in the furnace chamber is controlled at 100Kpa, and cooling begins after the addition is completed. Then the product is moved from the vacuum powder collecting dish to a vacuum environment to obtain a boron-aluminum alloy powder for standby use. Clean the plasma spheroidization equipment, use hot air to preheat the oven, the hot air temperature is 200℃, the preheating time is 1h, after debugging, adjust the equipment power to 25kW, let the plasma torch start to heat up, when the temperature of the plasma torch reaches 25000K, add 0.8% of the total mass of the boron-aluminum mixed powder with a particle size of 100-200nm at a constant carrier gas flow rate and powder feeding rate of 15L / min and 15g / min, and the nano-aluminum powder is instantly vaporized into aluminum vapor. Then immediately add the spare boron-aluminum alloy powder, and adjust the pressure in the reactor to 100Kpa. Under the action of internal pressure, the boron-aluminum alloy particles are coated by the vaporized aluminum powder (aluminum vapor) and condensed into powder. After reaching room temperature, a boron-aluminum alloy with a spherical composite layer structure is obtained.
[0074] Microstructure: The obtained boron aluminum alloy with spherical composite layer structure is a boron aluminum alloy AlB2 and AlB coated with aluminum as shell. 12The boron-aluminum alloy nanopowder with a core-shell structure has a powder spheroidization rate of 78%. The boron-aluminum alloy powder with a spherical composite layer structure obtained after two plasma spheroidization treatments has a particle size distribution between 0.8-1μm.
[0075] The properties of the boron-aluminum alloy powder with spherical composite layer structure before plasma spheroidization and after plasma spheroidization were determined as follows: a) Bulk density: The bulk density of boron-aluminum mixed powder is 0.80g / cm 3 Increase to 1.01g / cm of fine spherical boron aluminum alloy powder 3 , the loose density and tap density of the powder are significantly improved.
[0076] b) Fluidity: The fluidity of the boron-aluminum mixed powder before spheroidization is 105s / (100g), and the fluidity of the boron-aluminum alloy powder with a spherical composite layer structure obtained after spheroidization is 61s / (100g), which is significantly higher than that of the boron-aluminum mixed powder that has not undergone plasma spheroidization treatment, and the powder fluidity is improved.
[0077] c) Combustion performance: The combustion calorific value and combustion efficiency of the single boron powder, single aluminum powder before mixing treatment and the boron aluminum alloy powder with a spherical composite layer structure obtained after two plasma spheroidization treatments were tested respectively. The results showed that when the content of AlB2 and AlB12 alloy phases in the boron aluminum alloy powder was 56.9%, the combustion calorific value of the boron aluminum alloy powder could reach 36.6 MJ / kg, which was 138.5% higher than that of amorphous boron powder. The corresponding combustion efficiency was 79.2%, which was 54.1% higher than that of amorphous boron powder. At the same time, the AlB2 content in the boron aluminum alloy powder has an important influence on the thermal oxidation performance of the boron aluminum alloy powder. As the AlB2 content in the prepared boron aluminum alloy powder increases, its oxidation starting temperature, oxidation peak temperature and oxidation termination temperature gradually increase, and are all higher than those of amorphous boron powder. AlB2 and AlB12 in the alloy powder 12 The increase in content causes more high-melting-point composite oxides to form during the combustion and oxidation process, reducing the presence of liquid B2O3 on the surface of the alloy powder, thereby allowing the alloy powder to be more fully exposed to oxygen for oxidation and release more heat energy.
[0078] Example 4: Select D 50Aluminum powder and boron powder between 10-50μm are fully mixed in different mass ratios and then granulated: first, the composite solvent formula added to 1000g of boron-aluminum mixed powder is: 400ml n-hexane, 30g HTPB, 4ml curing agent HDI, and the mass concentration of polyvinyl alcohol solution is 5%, and then stirred at 350rpm for 20min. After stirring, it is cut at 1500rpm for 15min to obtain boron-aluminum composite particles. The powder after granulation is dried, that is, the obtained boron-aluminum composite particles are placed in a vacuum oven and dried at 200℃ for 8 hours. The dried boron-aluminum composite particles are subjected to plasma spheroidization treatment: first, the plasma spheroidization equipment is preheated by hot air in the oven, the hot air temperature is 150°C, the preheating time is 0.5h, argon is used as the carrier gas, and the boron-aluminum composite particles are added to the equipment under the conditions of a carrier gas flow rate of 25L / min and a powder feeding rate of 20g / min. The pressure in the furnace chamber is controlled at 100Kpa. After the addition is completed, cooling begins, and then the product is moved from the vacuum powder collecting dish to a vacuum environment to obtain boron-aluminum alloy powder for standby use. Clean the plasma spheroidization equipment, use hot air to preheat the oven, the hot air temperature is 200℃, the preheating time is 1h, after debugging, adjust the equipment power to 25kW, let the plasma torch start to heat up, when the temperature of the plasma torch reaches 30000K, add 1% of the total mass of the boron-aluminum mixed powder with a particle size of 100-200nm at a constant carrier gas flow rate and powder feeding rate of 25L / min and 20g / min, and the aluminum powder is instantly vaporized into aluminum vapor. Then immediately add the spare boron-aluminum alloy powder, and adjust the pressure in the reactor to 100Kpa. Under the action of internal pressure, the boron-aluminum alloy particles are coated by the vaporized aluminum powder (aluminum vapor) and condensed into powder. After cooling to room temperature, a boron-aluminum alloy with a spherical composite layer structure is obtained.
[0079] According to the above method, aluminum-coated boron-aluminum alloy micron particles with core-shell structure at different aluminum and boron ratios are obtained.
[0080] Microstructure: The obtained aluminum-coated boron aluminum alloy micron particles with core-shell structure have a powder spheroidization rate of 86%. The particle size distribution of the boron aluminum alloy powder after plasma spheroidization is between 15-45μm.
[0081] Combustion performance: The combustion calorific value and combustion efficiency of the single boron powder, single aluminum powder and boron aluminum alloy powder after two plasma spheroidization treatments were tested respectively. The results showed that the combustion calorific value of the boron aluminum alloy powders with different boron powder proportions was higher than that of amorphous boron powder and nano aluminum powder. When the mass ratio of boron powder to aluminum powder was 2:3, the combustion calorific value reached 30.4MJ / kg and the combustion efficiency was 68.7%; when the mass ratio of boron powder to aluminum powder was 13:7, the combustion calorific value reached 33.8MJ / kg and the combustion efficiency was 72.2%; when the molar ratio of boron aluminum mixed powder was 2:1, the AlB2 and AlB2 in the sintered product were 2:1, and the combustion efficiency was 72.2%. 12 It has the highest content, with a combustion calorific value of 35.9 MJ / kg and a combustion efficiency of 78.1%.
[0082] Comparative Example 1: Taking the boron-aluminum mixed powder with a mass percentage of 60% boron powder as an example, select D 50 Aluminum powder and boron powder between 0.9-1μm are fully mixed, then placed in a vacuum oven and dried at 200℃ for 8 hours to obtain a boron-aluminum mixed powder. The plasma spheroidization equipment is preheated with hot air, the hot air temperature is 150℃, the preheating time is 0.5h, argon is used as the carrier gas, the power is set at 20kW, the initial carrier gas flow rate is 5L / min, the initial powder feeding rate is 10g / min, and the gas flow rate is 0.5L / min and the powder feeding rate is 1g / min. The conditions of increasing the speed are increased to a maximum carrier gas flow rate of 25L / min and a maximum powder feeding rate of 20g / min and then kept constant, and the boron-aluminum mixed powder is added to the equipment, the pressure in the furnace chamber is controlled at 100KPa, and it is cooled after the addition is completed. Then the product is moved from the vacuum powder collecting dish to a vacuum environment to obtain a boron-aluminum alloy powder.
[0083] Combustion performance: The combustion calorific value and combustion efficiency of the boron aluminum alloy powder obtained by the primary plasma treatment were tested, and the results showed that the combustion calorific value was 17.1 MJ / kg and the combustion efficiency was 37.0%, which were significantly lower than the combustion performance of the alloy obtained by aluminum coating in Example 1. The reason for the above results is that when the boron aluminum alloy powder without the spherical composite layer is burned, the liquid boron dioxide, the combustion product of boron, will form on the powder surface, reducing the contact channel between the combustible powder and oxygen, resulting in incomplete combustion.
[0084] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this profession can make some changes or modifications to equivalent embodiments of equivalent changes by using the methods and technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.
Claims
1. A boron aluminum alloy having a spherical composite layer structure, characterized in that: The boron aluminum alloy has a core-shell structure in which aluminum is used as a shell layer to cover the boron aluminum alloy phase. The raw material composition of the boron aluminum alloy includes, by weight percentage: 35-60% aluminum powder and 40-65% boron powder; and the aluminum powder has a D 50 is 0.9~1μm or 10~50μm, and the D 50 ≤4μm.
2. The method for preparing the boron-aluminum alloy with a spherical composite layer structure according to claim 1, characterized in that: The method comprises the following steps: S1: mixing boron powder and aluminum powder according to a ratio, and drying to obtain a boron-aluminum mixture; S2: preheating the plasma spheroidizing equipment, and then adding the boron-aluminum mixture for high-temperature plasma treatment to form boron-aluminum alloy powder; S3: The plasma spheroidization equipment is cleaned, preheated and pre-debugged, and then aluminum powder is added to gasify the aluminum powder into aluminum vapor, followed by adding boron aluminum alloy powder to condense into powder, and finally cooled to room temperature to obtain a spherical composite layer structure of a boron aluminum alloy phase with a core-shell structure with aluminum as the shell layer covering the boron aluminum alloy phase.
3. The preparation method according to claim 2, characterized in that: In step S1, the mixing further includes a granulation step; The granulation process is as follows: adding a composite solvent to the boron-aluminum mixed powder, stirring and cutting, and obtaining boron-aluminum composite particles.
4. The preparation method according to claim 3, characterized in that: The composite solvent comprises: n-hexane, HTPB, curing agent HDI and polyvinyl alcohol solution; The amount of composite solvent added to every 1000g of boron-aluminum mixed powder is: 400ml of n-hexane, 30g of HTPB, 4ml of curing agent HDI, and the mass concentration of the polyvinyl alcohol solution is 5%.
5. The preparation method according to claim 3, characterized in that: The stirring speed is 300-400 rpm, and the stirring time is 15-30 min.
6. The preparation method according to claim 3, characterized in that: The cutting speed is 800-2000 rpm, and the cutting time is 15-30 min.
7. The preparation method according to claim 2, characterized in that: In step S1, the drying conditions are: temperature 180-200°C, time 8-12h.
8. The preparation method according to claim 2, characterized in that: In step S2, the high temperature plasma treatment conditions are: argon is used as the carrier gas, the power is set at 20-25 kW, the carrier gas flow rate is 5-25 L / min, the powder feeding rate is 10-20 g / min, and the pressure in the furnace chamber is controlled at 80-100 KPa.
9. The preparation method according to claim 2, characterized in that: In step S3, the pre-debugging conditions are: argon is used as the carrier gas, the power is set at 20-25 kW, the carrier gas flow rate is 5-25 L / min, the powder feeding rate is 10-20 g / min, and the plasma torch temperature is 20000-30000 K.
10. The preparation method according to claim 2, characterized in that: In step S3, after adding the boron aluminum alloy powder, the pressure is adjusted to 100-120 KPa.
Citation Information
Cited By
Manufacturing method of high-strength and high-hardness steel wheel
CN120269303A